Prognostic Value of Retinal Microvascular Alterations Detected by Fundus Examination in Critically Ill Patients: A Meta-Analysis - Ramzi Amin; Faiz Muhammad Ikhsan (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: The ocular fundus provides a unique window into the human microcirculation. Retinal microvascular alterations (RMVAs), such as hemorrhages, cotton wool spots, and vessel caliber changes, are observed in critically ill patients and may reflect systemic microvascular dysfunction, a key element in the pathophysiology of critical illness and organ failure. However, the prognostic significance of these findings in the intensive care unit (ICU) setting remains uncertain due to variability among individual studies. This meta-analysis aimed to synthesize existing evidence on the association between RMVAs detected by fundus examination and mortality in critically ill adult patients. Methods: We conducted a systematic literature search across PubMed, Embase, Scopus, and Web of Science databases for observational studies published between January 1st, 2013, and December 31st, 2023. Studies evaluating the association between RMVAs during ICU stay and mortality in adult ICU patients were included. Two reviewers independently performed study selection, data extraction, and quality assessment using the Newcastle-Ottawa Scale (NOS). Data on the presence versus absence of any significant RMVA and mortality were pooled using a random-effects model to calculate an overall odds ratio (OR) with a 95% confidence interval (CI). Heterogeneity was assessed using the I² statistic and Cochrane's Q test. Results: Our search yielded 1,872 unique records, of which 28 were assessed in full text. Six cohort studies, published between 2015 and 2023, met the inclusion criteria, encompassing a total of 1,358 critically ill patients. The included studies varied in population characteristics (medical, surgical, mixed ICUs) and methods of RMVA assessment. The overall quality of included studies was moderate to good (median NOS score 7, range 6-8). The prevalence of any significant RMVA ranged from 18% to 45% across studies. The pooled analysis demonstrated a statistically significant association between the presence of any RMVA detected on fundus examination and increased odds of mortality (Pooled OR = 2.48; 95% CI: 1.65–3.71; p < 0.0001). Moderate heterogeneity was observed among the studies (I² = 58%; p = 0.03 for Cochran's Q test). Conclusion: The presence of retinal microvascular alterations identified through fundus examination during ICU stay is significantly associated with an increased risk of short-term mortality in critically ill adult patients. These alterations may serve as an accessible marker of underlying systemic microvascular pathology and disease severity. Further large-scale, prospective studies with standardized protocols are warranted to confirm these findings and explore the utility of specific retinal signs.